(untitled) (Praxis Educativa, 2024)
The study investigates the effect of reflective thinking practices on retention scores using a mixed meta-method approach, which involves analyzing quantitative and qualitative data obtained through document reviews with meta-analysis and meta-thematic analysis. For the meta-analysis, nine studies that met the inclusion criteria in specific databases were identified. Using CMA and MetaWin programs, the meta-analysis revealed a significant effect size of g=1.550 across all nine studies, indicating that reflective thinking practices positively influence retention scores. The meta-thematic analysis, which included content analysis of 13, revealed the following four themes: contribution of reflective thinking practices to the learning process, benefits for students, obstacles associated with these practices, and suggested solutions to overcome them. The findings from both the meta-analysis and the meta-thematic analysis consistently support the conclusion that reflective thinking practices have a positive effect on retention.